2012
DOI: 10.31018/jans.v4i1.228
|View full text |Cite
|
Sign up to set email alerts
|

Study on eggs of Japanese quail (Coturnix coturnix japonica) during incubation in the controlled laboratory conditions

Abstract: Study on newly laid eggs of Japanese quail Coturnix coturnix japonica was undertaken for a period of 18 days on incubation in controlled laboratory conditions. The aim of the study was to evaluate the changes in egg weight, shell weight, yolk weight and embryo weight throughout the period of incubation. It had been found that as the embryo grows, the egg weight slowly goes down while embryo weight goes on increasing day by day. The study inferred that the shift or reduction in weight of egg is attributable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Yoshizaki et al (2004) reported a peak of yolk volume at day 4 of incubation in Japanese quail. This is consistent withBhagat, Zade, and Charde (2012) who recorded (wet) weight changes of the yolk sac in Japanese quail during the entire incubation period. Their data show a clear peak of yolk weight at day 4 of incubation.…”
supporting
confidence: 92%
“…Yoshizaki et al (2004) reported a peak of yolk volume at day 4 of incubation in Japanese quail. This is consistent withBhagat, Zade, and Charde (2012) who recorded (wet) weight changes of the yolk sac in Japanese quail during the entire incubation period. Their data show a clear peak of yolk weight at day 4 of incubation.…”
supporting
confidence: 92%
“…The selected eggs were sterilized with a 2:1 formaldehyde (37%):potassium permanganate (99%) solution [ 15 ] and incubated at 37.5°C and 60% humidity [ 16 ] in an automatic incubator (Luna 480; ChocMaster, Piraquara, Brazil). The automatic egg-turning tray turned the eggs every two hours until day 15 of incubation [ 17 ]. After 21 days of incubation, the numbers of hatched and fertilized but unhatched eggs were counted, and percent fertility was calculated.…”
Section: Methodsmentioning
confidence: 99%